The effect of heterophilic antibody interference in thyroglobulin measurement on different immunoassay devices - Kutluay Ismet Gamze; Bozdayi Mehmet Akif; Ulusal Hasan; Tarakcioglu Mehmet (Türk Biyokimya Dergisi, 2023)
Serum thyroglobulin (Tg) is a biochemical marker used in the follow-up of patients with differentiated thyroid cancer (DTC), but heterophile antibody interference may limit the clinical use of Tg.